2006
DOI: 10.1177/107110070602701115
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Factors Associated with Symptomatic Achilles Tendinopathy

Abstract: Obesity, hypertension, and steroids have as their end-organ effect a diminution of local microvascularity. The significant correlation of these factors with Achilles tendinopathy suggests the importance of their effect on microvascularity in the development of Achilles tendinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
173
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(180 citation statements)
references
References 43 publications
3
173
1
3
Order By: Relevance
“…Tendinopathy has an increased incidence with age and the male gender [11,89] and with obesity [36,47]. Excessive long-distance running, intensity, and hill work are risk factors for acute Achilles tendinopathy [60,70,95]; distance and excessive time spent swimming are associated with supraspinatus tendinopathy [98].…”
Section: Common Intrinsic and Extrinsic Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tendinopathy has an increased incidence with age and the male gender [11,89] and with obesity [36,47]. Excessive long-distance running, intensity, and hill work are risk factors for acute Achilles tendinopathy [60,70,95]; distance and excessive time spent swimming are associated with supraspinatus tendinopathy [98].…”
Section: Common Intrinsic and Extrinsic Associationsmentioning
confidence: 99%
“…Excessive long-distance running, intensity, and hill work are risk factors for acute Achilles tendinopathy [60,70,95]; distance and excessive time spent swimming are associated with supraspinatus tendinopathy [98]. There is also an association between tendinopathy and hormone replacement therapy and oral contraceptives in women [47].…”
Section: Common Intrinsic and Extrinsic Associationsmentioning
confidence: 99%
“…45,59 The less active are not immune as a minority of cases have been reported in sedentary groups. 43,107 Although runners appear to be the most commonly affected cohort, 59,60,62,98 Achilles disorders have been reported in a wide variety of sports. 32,33,59,60,134 It was noted that athletes are more likely to become symptomatic when training as opposed to during competitive events.…”
Section: Prevalencementioning
confidence: 99%
“…43 It has been suggested that these diseases diminish the blood flow that may ultimately reach the Achilles tendon. 43 These disease processes in part explain the prevalence of this disorder in the sedentary population. Interestingly, Achilles tendinopathy has been reported in 6% of cases after taking the antibiotic fluoroquinolone.…”
Section: Pronationmentioning
confidence: 99%
“…These results indicate a pivotal role for estradiol in maintaining homeostasis of female connective tissue. connective tissue; tendon fibrils; insulin-like growth factor-I; extracellular matrix; bone CROSS-SECTIONAL FINDINGS INDICATE that sex hormones influence tendon biomechanical properties (36), extracellular matrix adaptability in response to mechanical loading (11,21,36,41,59), and the risk of sustaining soft tissue injuries (11,24,25).…”
mentioning
confidence: 99%